A rhombus–keyhole shaped circularly polarized dual-band implantable antenna with low SAR compliance - Nagarajan Vasugi; Madurakavi Karthikeyan (PLoS ONE, 2026)
A compact dual-resonance implantable antenna with circular polarization (CP) has been proposed in this paper for bio telemetry applications. The antenna, with dimensions of 9 × 9 × 1 . 2 7 m m 3 , is designed using a reversed L-shaped patch, dual key-hole shaped structures and a central rhombus-shaped element. A shoring pin is employed to achieve dual-band resonance, while structural modification enables circular polarization. The proposed antenna resonates at 1.4 GHz (WMTS band) and 2.45 GHz (ISM band). The antenna is fabricated and measured using minced pork meat and saline solution. The measurement results show good agreement with the simulation results. Further, the SAR analysis and link budget analysis, prove that the antenna is suitable for real-time applications.